The unspoken plight of married adolescent girls in rural Tamil Nadu: Narrative summary on unmet sexual and reproductive health needs and barriers - Rasweth, Shreeya; B , Nisha (Indian Journal of Community Health, 2022)
Background: Young women who marry as adolescents face a number of sexual and reproductive health (SRH) issues. This study aimed to identify unmet SRH needs of adolescent girls and barriers they face in achieving them in rural Tamilnadu, India. Methodology: This qualitative study used narratives to understand participants and their immediate family’s SRH needs and barriers based on World Health Organization (WHO) guidelines. Totally, 14 in-depth interviews with young women and 14 focus group discussions with family members were conducted. The collected data were recorded digitally and transcribed verbatim and analysed by content analysis method. Results: Unmet SRH needs, primarily constituted of family planning methods, menstrual hygiene, sexual health, and Sexually Transmitted Diseases STD awareness. Barriers to healthcare access are societal stigma, taboos, intimate partner violence, and early marriage. Conclusions: The topic of family planning was taboo, menstruation as a negative influence on their daily activities, engaging in sexual activities was to provide sexual pleasure to their partners, to comply with their partners' wishes when under the influence of alcohol, and to produce children and lack of education regarding obtaining consent for sexual activity. We can conclude that it is important to understand how the SRH needs of adolescent girls can be met and need better-suited policies and services.